Molecular characterization of partial fusion gene and C-terminus extension length of haemagglutinin-neuraminidase gene of recently isolated Newcastle disease virus isolates in Malaysia. - Berhanu , Ayalew; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (Springer, 2010)
Newcastle disease (ND), caused by Newcastle disease virus (NDV), is a highly contagious disease of birds and has been one of the major causes of economic losses in the poultry industry. Despite routine vaccination programs, sporadic cases have occasionally occurred in the country and remain a constant threat to commercial poultry. Hence, the present study was aimed to characterize NDV isolates obtained from clinical cases in various locations of Malaysia between 2004 and 2007 based on sequence and phylogenetic analysis of partial F gene and C-terminus extension length of HN gene.